An Investigation into the Role of Language in Regional Connectivity in Afghanistan and Pakistan - Nasim Gul; Dr. Salma Khatoon; Dr. Syed Sabih Ul Hassan (University of Chitral Journal of Linguistics and Literature, 2022)
This article intends to explore the role of the regional language Pashto spoken in Afghanistan and Pakistan in regional connectivity. The aim of this study is to reveal whether the role of Pashto language is positive or negative in the regional connectivity between the two neighbouring countries. The impacts of Pashto on Pakistan and Afghanistan cultures are taken into consideration because it is claimed that language is culture and culture is language. Furthermore, Sapir (1921) also added that due to the close association of language and culture, with each other, one cannot be understood/appreciated without the knowledge/comprehension of the other. It implies that the present study investigates the correlation between Pashto language and Pashtun culture in both countries. The data for this study is collected from Pashto language Poets, authors, MPhil, and PhD scholars belonging to Pakistan and Afghanistan. The findings of the study revealed that the regional language Pashto plays a vitally important role in regional connectivity between Pakistan and Afghanistan. The study also found that people of both countries are inclined towards the purification and learning of Pashto language along with the learning of English language in the same territories. Therefore, they are also learning culture and social norms in both countries alike. The findings of the study also revealed that Pashto language in both countries can be used as a tool for dialogues to strengthen peace, trade, and business.